A novel simple practical thermal-hydraulic-mechanical (THM) coupling model with water-ice phase change. (February 2020) - Li, Guofeng; Li, Ning; Bai, Yue; Liu, Naifei; He, Mingming; Yang, Min
Graphical abstract: Abstract: To reduce the threat from freeze-thaw weathering and to improve the safety of projects in permafrost areas, it is necessary to research freeze-thaw failure mechanisms and engineer safeguarding measures. Therefore, it is essential and effective to develop a reasonable, simple, practical and accurate thermal-hydraulic-mechanical (THM) coupling model with water-ice phase change. A simple model is embedded in the FLAC3D software package using FISH language. The model is developed by combining an ice-water phase change model and the THM coupling model. It is verified and extended via the uniform freeze-thaw test and the unidirectional freeze-thaw test, respectively. The results of the tests are in good agreement with laboratory tests, showing that the simplified algorithm is feasible. The favourable practical ability of the developed THM model makes it well suited for use in exploring multi-field change laws. It is an effective tool for analysing freeze-thaw failure mechanisms and engineering safeguard measures in permafrost regions.